An economic analysis of agri-food firms’ resiliency: a case study of six companies - Locke, Steven M (Kansas State University, 2024)
The thesis examines resilience of a select group of companies in the agri-food sector and outside the sector. The agri-food firms selected are ADM, Coca-Cola, PepsiCo, Conagra, AGCO, and Tyson. The non-agri-food firms are DISH, Walmart, Ford, ExxonMobil. ADM and AGCO are upstream in the agri-food chain while the others are processors. Similarly, Ford and ExxonMobil are manufacturers, DISH is a service provider, and Walmart is a comprehensive retailer. With monthly gross profit margin from the Wharton Research Data Service and macroeconomic shocks from the Federal Research of St. Louis, National Bureau of Economic Research, Bureau of Labor Statistics, and other public agencies, the research explored the relationship between gross profit margins of selected firms and the interaction between whether there was an adverse macroeconomic event the traditional indicators of such events – unemployment rate, interest rate, inflation rate, and labor participation rate. The results showed that while the majority of the firms experienced the expected negative sign on their coefficients for adverse macroeconomic shocks, the coefficients were not statistically significant. However, Coca-Cola and ExxonMobil had statistically significant negative coefficients, indicating that the gross profit margins of these two companies were adversely affected by the adverse macroeconomic events. We do not draw any inferential conclusions from this study because the companies were purposively selected, and they were all large publicly traded companies. It is suggested that future work use a more formalized sampling approach for firms, such as random sampling and consider multiple performance indicators.
Keywords: Resilience; Gross profit margin; Agri-food; Agri food; Crisis